The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1016/j.resconrec.2010.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of recycled base materials with high carbon fly ash

Abstract: A study was conducted to stabilize low stiffness road surface material with high carbon fly ash. The non-cementitious Maryland fly ash was activated with another recycled material, lime kiln dust (LKD). California bearing ratio (CBR) and resilient modulus tests were conducted to determine the strength and stiffness, respectively, of the stabilized materials. Addition of LKD and curing of specimens generally increased CBR and summary resilient modulus (SM R ) and lowered plastic strains, whereas fly ash additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(44 citation statements)
references
References 15 publications
5
35
0
1
Order By: Relevance
“…The reason for the increase in the optimum water content is an increase in the particle surface area of samples due to the addition of finer materials. Similar trends have been obtained from some experimental works [3,4,5,6,7].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The reason for the increase in the optimum water content is an increase in the particle surface area of samples due to the addition of finer materials. Similar trends have been obtained from some experimental works [3,4,5,6,7].…”
Section: Resultssupporting
confidence: 89%
“…There are a lot of studies about fly ash used in the stabilization of soils. In the previous studies [2,3,4,5,6,7] it was indicated that the engineering properties of fly ash amended soils have been improved. Generally, fly ash was used together with different additive materials like cement, lime or industrial wastes like marble dust, cement kiln dust, etc.…”
Section: Introductionmentioning
confidence: 99%
“…This reaction of fly ash with lime in concrete improves strength. Cetin et al [11] reported that the CBR value of the soil stabilized with fly ash (10% and 20%) and lime kiln dust (2.5% and 5%) were found to be In the same way, alternate layers of fly ash overburden admixture and overburden only was filled in the void. Thus, each layer of admixture of fly ash overburden was followed by a layer of overburden.…”
Section: Mechanism Of Stabilization Of Slope With Fly Ashmentioning
confidence: 92%
“…The use of recycle materials in pavement systems in lieu of natural aggregates has been an interest for some time (Tanyu et al 2005;Li et al 2009;Cetin et al 2010). Crushed waste concrete, termed recycled concrete aggregate (RCA), is also considered as an alternative material to be used in roadway construction (Chen et al 2013).…”
Section: Introductionmentioning
confidence: 99%